Risk communication in flood-prone communities: memories, informal practices and public action in Brazil - Mário Henrique da Mata Martins; Fernanda Lima-Silva; Caio Cruz; Maria Alexandra Viegas Cortez da Cunha (Interface: Comunicação, Saúde, Educação)
Current studies on risk communication often rely on either top-down or bottom-up approaches, with a notable lack of integration between these processes. This article explores this disconnect, presents a public action framework specifically tailored to integrate top-down and bottom-up analysis of flood risk communication, apply it to examine flood memories and identify types of flood risk communication in vulnerable communities. These flood memories provide crucial insights into community experiences and interpretations of risk communication, enhancing strategies for future events. The study employs qualitative approaches, including interviews and content analysis. Results indicate that while formal risk communication may be limited, informal channels, word-of-mouth, and practices related to flood memory, community events and local organizations are present. The public action approach emerges as a valuable strategy for understanding local nuances in flood risk communication in vulnerable communities.